Understanding the colorimetric properties of quinoxaline-based pi-conjugated copolymers by tuning their acceptor strength: a joint theoretical and experimental approach. Issue 36 (21st April 2017) - Fagour, Sébastien; Thirion, Damien; Vacher, Antoine; Sallenave, Xavier; Sini, Gjergji; Aubert, Pierre-Henri; Vidal, Frédéric; Chevrot, Claude
Abstract : We report the synthesis and characterization of donor–acceptor π-conjugated copolymers leading to blue-to-green coloration according to acceptor strength. Abstract : A series of five new π-conjugated donor–acceptor–donor (DAD n ) copolymers are presented, combining a common donating unit (substituted propylenedioxythiophene, ProDOT-(OEtHx)) with five diphenyl-quinoxaline based acceptor units bearing substituents of increasing acceptor strength (OMe < H < F < COOMe < CN). The DAD n copolymers, namelyP3-X (X = OMe, H, F, COOMe, CN), have been studied in solid state by cyclic voltammetry to investigate their electronic properties during n- and p-doping processes and to determine their electrochemical band gap. UV-Vis spectroscopy reveals a dual-band absorption system in which both high energy and low energy band (HEB and LEB) positions and intensities are governed by the acceptor strength. Density functional theory (DFT) computations were performed on D–A–D trimer model compounds in order to understand the experimental results. A colorimetric study in the CIELAB color space revealed that the modulation of the acceptor strength with σ- or π-electron withdrawing/donating groups leads to shades of blue to green upon increasing the acceptor strength. The polymers can also switch to a grey color upon p-doping. Finally, a detailed discussion on color–structure relationship provides valuable insights on molecular design principles to render cyan and green colors.